COVID-19 AND ACCESS TO REPRODUCTIVE HEALTH RIGHTS FOR WOMEN IN HIGHER EDUCATION INSTITUTIONS IN SOUTH AFRICA (The Pretoria Student Law Review, 2021)
Reproductive health rights are rights that are internationally and domestically recognised as human rights. The right to contraception forms part of reproductive health rights. These rights have a great impact on the social, political, and economic well-being of women. This paper studies the impact that COVID-19 has had on health, specifically on access to contraceptives, as these services have not been deemed as essential during the lockdown. The lockdown has seen the closure of higher education institutions like colleges, Technical Vocational Education and Training (TVET) colleges, universities, and universities of technologies, where the majority of women who depend on public health facilities access their contraceptives, resulting in these women having to access contraceptives from their home communities. This paper further studies the challenges that these women face in accessing contraceptives from their homes, such as stigma and the lack of information that accompanies it. Lastly, this paper finds that the women that access their contraceptives in institutions of higher learning do not have any alternatives. It finds that the closure of these institutions has resulted in these women being stranded without contraceptives, resulting in a violation of their reproductive health rights.
Keywords: contraceptives; COVID-19; institutions of higher education; reproductive health rights